Outcomes of medical and surgical treatment for intestinal fistulizing Crohn’s disease - Pingrun Chen; Yufen She; Liangfang Wang; Yina Li; Yan Zhang (PLoS ONE, 2025)
Background Intestinal penetrating complications of Crohn’s disease (CD) are challenging issues, but it is difficult to decide between medical treatment and surgery. This study aimed to evaluate the outcomes of medical and surgical therapy in patients with non-perianal fistulizing CD. Objective Our study aimed to evaluate and compare the effectiveness of surgery and medical treatment in CD patients with non-perianal fistulas. Materials and methods This retrospective study included all CD patients with non-perianal fistulas. We evaluated the outcomes of medical and surgical therapy. Fistula closure was identified with radiological examinations or ultrasound. Cox regression analysis was subsequently performed. Results Sixty patients (37 male) were included. 43.3% of the patients received biological agents as the first therapy, whereas 55% required surgery as the initial therapy, and the remaining 1 patient received azathiopurine alone. 71.7% of the patients achieved fistula closure, with a median follow-up of 32 months. Among the patients who received biologics as the initial treatment, 38.5% achieved fistula closure without the need for surgery, and 50% of the patients underwent surgery. Fistula closure was observed in 69.7% of the patients who underwent surgery as the initial treatment. Enteral nutrition before initial treatment was independently associated with fistula closure. Conclusion Although surgery occupies a crucial role in the treatment of patients with non-perianal fistulizing CD, biologics are also effective. Enteral nutrition may increase the probability of fistula closure, especially in patients who undergo surgery as the initial therapy.